EVALUATION OF DRUG INTERACTION RISK AND PATTERNS IN HYPERTENSIVE PATIENTS WITH COMORBIDITIES IN A HOSPITAL SETTING - Eka Putri Nurhidayah (SOCIAL CLINICAL PHARMACY INDONESIA JOURNAL, 2025)
Hypertension is a chronic condition with a high prevalence and is frequently accompanied by comorbidities that require polypharmacy, thereby increasing the risk of drug–drug interactions (DDIs). This study aimed to evaluate the risk and patterns of DDIs among hypertensive inpatients with comorbidities using a retrospective observational design based on medical record data from 2023–2024. Descriptive analysis was performed on patient characteristics, antihypertensive regimens, and potential DDIs using scientific literature and standardized interaction-checking tools (Medscape, DrugBank, Drugs.com). Validation was conducted independently by a clinical pharmacy practitioner and a clinical pharmacy researcher. Of the 182 medical records reviewed, 65 met the inclusion criteria. Most patients were aged ≥60 years (56.9%) and female (55.4%). A total of 56.9% of patients experienced potential DDIs. Moderate-risk interactions most frequently involved pharmacodynamic mechanisms, particularly aspirin–furosemide, nifedipine–alprazolam, valsartan–insulin glargine, and candesartan–meloxicam. Major interactions were identified in combinations such as valsartan–spironolactone and ramipril–spironolactone, which may increase the risk of hyperkalemia, as well as diltiazem–bisoprolol, which has an additive effect on SA/AV nodal conduction.These findings highlight that hypertensive patients with comorbidities are at high risk for DDIs. Regular clinical monitoring and systematic medication review by clinical pharmacists are essential to enhance therapeutic safety and effectiveness in hospital settings.